Different components of chicken ovalbumin extract promote different cell proliferation - Ruan, G-P; Yao, X; Liu, J-F; Wang, J-X; Pan, X-H (Cellular and Molecular Biology, 2015)
The chicken ovalbumin extracts could promote cell survival and proliferation. In the present study, the different components in chicken ovalbumin extracts were further separated to find the component primarily responsible for promoting cell proliferation. Components of differing molecular weight were separated from chicken ovalbumin extracts by ultrafiltration. Different components were co”cultured with different cells at different final concentrations, and the effects on cell proliferation were subsequently determined by a CellTiter 96 Aqueous One Solution Cell Proliferation Assay kit (Promega). Components from chicken ovalbumin extracts less than 3 kD in size can promote 293T cell and 293T”GFP cell proliferation. The components from chicken ovalbumin extract more than 3 kD in size can promote bone marrow or umbilical cord mesenchymal stem cell (MSC) proliferation. The separation of components from chicken ovalbumin less than and more than 3 kD in size that are able to function as active components for the promotion of different cellular proliferation. This discovery may identify a new and convenient additive for cell culture media, promoting cell growth and proliferation.